2016
DOI: 10.1073/pnas.1602733113
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant thiopeptides containing noncanonical amino acids

Abstract: Thiopeptides are a subclass of ribosomally synthesized and posttranslationally modified peptides (RiPPs) with complex molecular architectures and an array of biological activities, including potent antimicrobial activity. Here we report the generation of thiopeptides containing noncanonical amino acids (ncAAs) by introducing orthogonal amber suppressor aminoacyl-tRNA synthetase/tRNA pairs into a thiocillin producer strain of Bacillus cereus. We demonstrate that thiopeptide variants containing ncAAs with bioort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 37 publications
0
65
0
4
Order By: Relevance
“…24, 42, 43 These latter pairs are especially advantageous as they allow aaRSs to be evolved in E. coli prior to transfer of the machinery to more diverse eukaryotic hosts. Utilizing these orthogonal pairs, ncAAs have been encoded in B. cereus, 89 P. pastoris, 90 C. elegans, 91, 92 D. melanogaster, 93 A. thaliana, 94 Zebrafish embryos, 95 and the mouse. 9699 More recently, it has been demonstrated that a native Trp aaRS/tRNA pair in E. coli can be functionally replaced with a counterpart from yeast, and the liberated Trp pair can be used to encode ncAAs in bacteria.…”
Section: Expanding the Genetic Codementioning
confidence: 99%
“…24, 42, 43 These latter pairs are especially advantageous as they allow aaRSs to be evolved in E. coli prior to transfer of the machinery to more diverse eukaryotic hosts. Utilizing these orthogonal pairs, ncAAs have been encoded in B. cereus, 89 P. pastoris, 90 C. elegans, 91, 92 D. melanogaster, 93 A. thaliana, 94 Zebrafish embryos, 95 and the mouse. 9699 More recently, it has been demonstrated that a native Trp aaRS/tRNA pair in E. coli can be functionally replaced with a counterpart from yeast, and the liberated Trp pair can be used to encode ncAAs in bacteria.…”
Section: Expanding the Genetic Codementioning
confidence: 99%
“…49, 50, 584, 599, 695, 696 These approaches are flexible and can be combined with amber codon suppression technology to include unnatural amino acids. 230, 599, 697 The use of unnatural amino acids has even allowed the creation of derivatives which can be labeled with fluorophores or other tags to aid in mode of action studies or visualization in cells. 230, 599 In general, in vivo combinatorial biosynthesis has seen been successful in generating diverse molecules given the wide ranges of compounds detected in culture which could be screened for desired activity.…”
Section: Biotechnologymentioning
confidence: 99%
“…230, 599, 697 The use of unnatural amino acids has even allowed the creation of derivatives which can be labeled with fluorophores or other tags to aid in mode of action studies or visualization in cells. 230, 599 In general, in vivo combinatorial biosynthesis has seen been successful in generating diverse molecules given the wide ranges of compounds detected in culture which could be screened for desired activity. A few individual compounds have been made in quantity, isolated and characterized using these methods, 599 but the success is limited as an acknowledged drawback is the low yields of most compounds made in this way and the difficulty in their isolation.…”
Section: Biotechnologymentioning
confidence: 99%
“…[122,123] Bei Konjugation mit einem Fluorophor-Azid werden die Zielproteine anschließend mit-tels SDS-PAGEa ufgetrennt und durch Fluoreszenz-Imaging des Gels visualisiert. [129][130][131] Die modernen Fortschritte haben die Massenspektrometrie als eine weit verbreitete und äußerst leistungsfähige Methode zur Analyse der zellulären Netzwerke von Metaboliten (Metabolomik) und Proteinen (Proteomik) etabliert. B. Biotin-Azid) angehängt wurde,k çnnen die Proteine durch Affinitätschromatographie angereichert und proteolytisch verdaut werden.…”
Section: Identifizierung Und Validierung Der Biologischen Zielstrukturunclassified